Adenosine in the Inflamed Gut: A Janus Faced Compound - B. Estrela, A.; Abraham, W.-R. (Current Medicinal Chemistry, 2011)
The purine ribonucleoside adenosine (Ado) has been recognized for its regulatory functions in situations of cellular stress like ischemia, hypoxia and inflammation. The importance of extracellular Ado as a modulator in the immune system is a theme of great appreciation and the focus of recent increasing interest in the field of gastrointestinal inflammation. In this review, the different aspects of Ado signaling during inflammatory responses in the gut are discussed, considering the contribution of the four known Ado receptors (ARs; A1, A2A, A2B, and A3), their mechanisms and expression patterns. Activation of these receptors in epithelial cells as well as in immune cells recruited to the inflamed intestinal mucosa determines the overall effect, ranging from a protective, anti-inflammatory modulation to a strong pro-inflammatory induction. Here we present the current advances in agonists and antagonists development and their potential therapeutic application studied in animal models of intestinal inflammation. In addition, alternative complementary approaches to manipulate such a complex signaling system are discussed, for example, the use of AR allosteric modulators or interference with Ado metabolism. Special features of the gut environment are taken into account: the contribution of diet components; the involvement of Ado in intestinal infections; the interactions with the gut microbiome, particularly, the recent exciting finding that an intestinal bacterium can directly produce extracellular Ado in response to host defense mechanisms in an inflammation scenario. Understanding each component of this dynamic system will broaden the possibilities for applying Ado signaling as a therapeutic target in gut inflammation.
Keywords: structure-activity relationships (SAR)